Multiplexing near- and far-field functionalities with high-efficiency bi-channel metasurfaces - Changhong Dai; Tong Liu; Dongyi Wang; Lei Zhou (PhotoniX, 2024)
Abstract Propagating waves and surface waves are two distinct types of light-transporting modes, the free control of which are both highly desired in integration photonics. However, previously realized devices are bulky in sizes, inefficient, and/or can only achieve one type of light-manipulation functionality with a single device. Here, we propose a generic approach to design bi-channel meta-devices, constructed by carefully selected meta-atoms possessing reflection phases of both structural-resonance and geometric origins, which can exhibit two distinct light-manipulation functionalities in near-field (NF) and far-field (FF) channels, respectively. After characterizing the scattering properties of basic meta-atoms and briefly stating the theoretical strategy, we design/fabricate three different meta-devices and experimentally characterize their bi-channel wave-control functionalities in the telecom regime. Our experiments show that the first two devices can multiplex the generations of NF and FF optical vortices with different topological charges, while the third one exhibits anomalous surface plasmon polariton focusing in the NF and hologram formation in the FF simultaneously. Our results expand the wave-control functionalities of metasurfaces to all wave-transporting channels, which may inspire many exciting applications in integration optics.